2011
DOI: 10.1002/esp.2200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ENSO events on sediment production in a large coastal basin in northern Peru

Abstract: Although the importance of ENSO on hydrological anomalies has been recognized, variations in sediment fluxes caused by these extreme events are poorly documented. The effect of ENSO is not limited to changes in sediment mobilization. Since ENSO events can affect terrestrial ecosystems, they may have important effects on sediment production and transport in river basins over time spans that are longer than the duration of the event itself. The Catamayo-Chira basin is an interesting casestudy for investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…in the east, where slopes are generally steep (>40%). The Catamayo River is the main river in the catchment with a length of 120 km, and is the main tributary of the Ecuadorian‐Peruvian hydrographic system (17,000 km 2 ), called the Catamayo–Chira, which drains into the Pacific Ocean (Tote et al ). Average annual water flow is 35 m 3 /s, which reduces significantly to 22 m 3 /s during the dry season (June–November) (Ochoa et al ).…”
Section: Study Areamentioning
confidence: 99%
“…in the east, where slopes are generally steep (>40%). The Catamayo River is the main river in the catchment with a length of 120 km, and is the main tributary of the Ecuadorian‐Peruvian hydrographic system (17,000 km 2 ), called the Catamayo–Chira, which drains into the Pacific Ocean (Tote et al ). Average annual water flow is 35 m 3 /s, which reduces significantly to 22 m 3 /s during the dry season (June–November) (Ochoa et al ).…”
Section: Study Areamentioning
confidence: 99%
“…For Andean catchments similar to the Santa and Tablachaca catchments, there are no published data about bedload yield. More to the north of Peru, in the Catamayo-Chira catchment, total sediment yield has been quantified with bathymetric monitoring of the Poechos reservoir (Tote et al, 2011). Unfortunately, these data cannot be compared to ours because the climate of the Catamayo-Chira catchment is impacted more by El Niño and La Niña events than that of the Santa and Tablachaca catchments, and because differences in the SSY vs. Q rating curves between these catchments reveal different sediment production and transport processes.…”
Section: Suspended Load/bedload Partitioningmentioning
confidence: 99%
“…For instance, Tote et al (2011) showed for a river basin in northern Peru that El Nino Southern Oscillation (ENSO) was responsible for the flushing of stored sediment, reversed during post-ENSO periods. For instance, Tote et al (2011) showed for a river basin in northern Peru that El Nino Southern Oscillation (ENSO) was responsible for the flushing of stored sediment, reversed during post-ENSO periods.…”
Section: The Geomorphic Signature Of High Frequency Climatic Variabilitymentioning
confidence: 99%
“…Given our ability to quantify variability over shorter timescales, a further trend is emerging: the ability to evaluate, across a range of different environments, geomorphic forcing by climatic variability at the scale of years to decades. For instance, Tote et al (2011) showed for a river basin in northern Peru that El Nino Southern Oscillation (ENSO) was responsible for the flushing of stored sediment, reversed during post-ENSO periods. Brook et al (2011) show that the area of small glaciers fluctuates in relation to the forcing of ablation by regional atmospheric circulation, notably the ENSO but also the Interdecadal Pacific Oscillation.…”
Section: The Geomorphic Signature Of High Frequency Climatic Variabilitymentioning
confidence: 99%